Synergistic effects of PGPRs and fertilizer amendments on improving the yield and productivity of Canola (Brassica napus L.) - Haji Muhammad; Muhammad Ijaz; Abdul Sattar; Sami Ul-Allah; Ahmad Sher; Muhammad Asif; Muhammad Dilshad; Khalid Mahmood; Muhammad Waheed Riaz; Muhammad Saqlain Zaheer; Muhammad Rizwan; Salim Manoharadas (BMC Plant Biology)
Abstract Background Organic fertilizers are safer and more eco-friendly than chemical fertilizers; hence, organic fertilizers can be used to support sustainable farming. The effects of PGPRs are manifold in agriculture, especially in monoculture crops, where the soil needs to be modified to increase germination, yield, and disease resistance. The objective of this study was to assess the effects of PGPRs combined with fertilizer on the yield and productivity of canola. Canola was chosen for its global importance as an oilseed crop and its responsiveness to soil amendments, making it ideal for evaluating the synergistic effects of PGPRs and fertilizers on yield and soil health. Methodology This research, which was carried out over two years, was aimed at establishing the effectiveness of PGPRs together with organic and inorganic fertilizers on canola yields and was performed with a two-factorial RCBD design under field conditions. We applied Azotobacter salinestris and Bacillus subtilis with biochar, compost, animal manure, poultry manure, and NPK fertilizer. Insect pest management and other agronomic practices were carried out to maintain the experiment. Results Canola yield and agronomic traits were enhanced by the combination of Bacillus subtilis with the fully recommended N: P:K ratio (140:55:40 kg/ha). Additionally, the application of Bacillus subtilis with biochar at 2 tons/ha improved the yield and quality of canola, as well as the structure and nutrient regulation of the soil. Conclusion In light of these results, we recommend the application of Bacillus subtilis to canola seeds along with either 2 t/ha biochar or the entire recommended dose of N: P:K (140:55:40 kg/ha). These strategies are sustainable and help producers and the environment increase the productivity of canola. Combining PGPRs with fertilizers for canola enhances nutrient efficiency, promotes sustainable growth, and boosts stress resilience, addressing agricultural and environmental challenges. Clinical trial number Not Applicable.